Bleisure a quantitative study on the destination as a factor in attending MICE events - Bernabe, Cynthia R.; Tagle, Isabel Beatriz; Amores, Anael; Francisco, Hazel; Winter, Myrrel (2019)
Bleisure is the act of mixing business travel with leisure or vacation time. With the rise of bleisure, this research aimed to study if a destination is a significant consideration for attendance to a MICE event. Moreover, this research answered the question of what are the other factors that would most affect the attendee's decision to come to the event. the study employed the quantitative research method and conducted an online survey to the participants holding a supervisory level in a business company that has attended MICE events. The study revealed that 70.1 % of the respondents agree that a destination affects their desire to attend an event. The results also showed that the primary factor that affects an attendee's decision to come to an event is the speaker, followed by the destination, the cost/budget, and their schedule. Based on this current study, we recommend to MICE organizers to plan events that would align with the desires of bleisure travelers and to the factors that influence their decision-making to come to an event.
Keywords: Business; Leisure; Events; Business travel; Vacations